Differential metabolic rearrangements in the roots and leaves of Cicer arietinum caused by single or double nitrate and/or phosphate deficiencies. (11th August 2022) - Nasr Esfahani, Maryam; Kusano, Miyako; Abdelrahman, Mostafa; Nguyen, Kien Huu; Watanabe, Yasuko; Mochida, Keiichi; Burritt, David J.; Tran, Lam‐Son Phan
SUMMARY: Nitrate (NO3 − ) and phosphate (Pi) deficiencies are the major constraints for chickpea productivity, significantly impacting global food security. However, excessive fertilization is expensive and can also lead to environmental pollution. Therefore, there is an urgent need to develop chickpea cultivars that are able to grow on soils deficient in both NO3 − and Pi. This study focused on the identification of key NO3 − and/or Pi starvation‐responsive metabolic pathways in the leaves and roots of chickpea grown under single and double nutrient deficiencies of NO3 − and Pi, in comparison with nutrient‐sufficient conditions. A global metabolite analysis revealed organ‐specific differences in the metabolic adaptation to nutrient deficiencies. Moreover, we found stronger adaptive responses in the roots and leaves to any single than combined nutrient‐deficient stresses. For example, chickpea enhanced the allocation of carbon among nitrogen‐rich amino acids (AAs) and increased the production of organic acids in roots under NO3 − deficiency, whereas this adaptive response was not found under double nutrient deficiency. Nitrogen remobilization through the transport of AAs from leaves to roots was greater under NO3 − deficiency than double nutrient deficiency conditions. Glucose‐6‐phosphate and fructose‐6‐phosphate accumulated in the roots under single nutrient deficiencies, but not under double nutrient deficiency, and higher glycolytic pathway activities were observed in both roots and leaves under single nutrient deficiency than double nutrient deficiency. Hence, the simultaneous deficiency generated a unique profile of metabolic changes that could not be simply described as the result of the combined deficiencies of the two nutrients. Significance Statement: There is no available information on the adaptive mechanisms, in terms of metabolic changes, which enable plants to respond to double nutrient nitrate (NO3 − ) and phosphate (Pi) starvation. The results of this study allow us to understand and discover promising key metabolic pathways responsive to single and/or double NO3 − and Pi starvation in chickpea plants, which can be targeted for genetic engineering to develop chickpea cultivars that are more productive in N‐ and/or Pi‐poor soils.